The Effect of Trial Periods in Employment on Firm Hiring Behaviour - Nathan Chappell; Isabell Sin (New Zealand Government, The Treasury, 2016)
An amendment to legislation in 2009 enabled New Zealand firms with fewer than 20 employees to hire new workers on trial periods. The scheme was subsequently extended to employers of all sizes. The policy was intended to encourage firms to take on more employees, and particularly more disadvantaged job seekers, by reducing the risk associated with hiring an unknown worker. We use unit record linked employer-employee data and the staggered introduction of the policy for firms of different sizes to assess the policy effect on firm hiring behaviour. We find no evidence that the policy affected the number of hires by firms on average, either overall or into employment that lasted beyond the trial period. We also do not find an effect on hiring of disadvantaged jobseekers. However, our results suggest that the policy increased hiring in industries with high use of trial periods by 10.3 percent.
Keywords: J08; J63; J64; 330; 90-day trials; employment; labour market flexibility; firm hiring; Arbeitsmarktreform; Befristete Beschäftigung; Dauer; Arbeitsmarktflexibilität; Beschäftigungseffekt; Neuseeland